2021
DOI: 10.12659/msm.930053
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-C Motif) Ligand 2/Chemokine Receptor 2 (CCR2) Axis Blockade to Delay Chondrocyte Hypertrophy as a Therapeutic Strategy for Osteoarthritis

Abstract: Background Chondrocytes play a vital role in the later stages of osteoarthritis (OA). The roles of chemokine (C-C motif) ligand 2 (CCL2) and its receptor, chemokine receptor 2 (CCR2), are as yet poorly elucidated in chondrocyte hypertrophy (CH). Here, we aimed to regulate the CCL2/CCR2 axis and explore its effect on progression of CH. Material/Methods Chondrocytes isolated from patients with OA were used in the present study. In vitro experiments were conducted to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Runtassociated transcription factor 2 (RUNX2) is a master transcription factor for chondrocyte hypertrophy that plays an important role in osteoarthritis [10]. Researchers have demonstrated that chondrocyte hypertrophic differentiation, a key process in endochondral ossification, is also a feature of osteoarthritis leading to cartilage destruction [10,11]. In addition, SFPQ could be competitively bound by various non-coding RNAs, thereby increasing the translation level of RUNX2 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Runtassociated transcription factor 2 (RUNX2) is a master transcription factor for chondrocyte hypertrophy that plays an important role in osteoarthritis [10]. Researchers have demonstrated that chondrocyte hypertrophic differentiation, a key process in endochondral ossification, is also a feature of osteoarthritis leading to cartilage destruction [10,11]. In addition, SFPQ could be competitively bound by various non-coding RNAs, thereby increasing the translation level of RUNX2 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…CCR2 is one of the more studied chemokine receptors in OA. CCR2 is upregulated in interleukin-17A-treated chondrocytes and protects type II collagen synthesis and attenuates the IL-17A-induced overexpression of RUNT-related transcription factor 2 by inhibiting CCR2 expression, thereby delaying the development of chondrocyte hypertrophy [55].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of the abovementioned studies, it can be hypothesized that copper cell death genes are crucial for immune infiltration in osteoarthritis; however, there have been few investigations into the involvement of copper cell death-related genes in the immune regulation of osteoarthritis. Antigen-presenting cells, mast cells, dendritic cells, and chemokine receptor 2 (CCR2) may have significant effects on the regulation of copper cell death genes in osteoarthritis [ 118 , 119 , 120 , 121 ] ( Figure 1 ).…”
Section: Mechanisms Of Cell Death In Osteoarthritismentioning
confidence: 99%